2002
DOI: 10.1128/cdli.9.2.403-411.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Bacterial Protein Adhesins on Toll-Like Receptors for Proinflammatory Cytokine Induction

Abstract: Toll-like receptors (TLRs) are important signal transducers that mediate inflammatory reactions induced by microbes through pattern recognition of virulence molecules such as lipopolysaccharide (LPS) and lipoproteins. We investigated whether proinflammatory cytokine responses induced by certain bacterial protein adhesins may also depend on TLRs. In differentiated THP-1 mononuclear cells stimulated by LPS-free recombinant fimbrillin (rFimA) from Porphyromonas gingivalis, cytokine release was abrogated by monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
108
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 57 publications
7
108
0
Order By: Relevance
“…Thus, they appear to be ideal ligands for a pattern recognition receptor. Interestingly, BspA interacts also with other pattern recognition receptors, such as the Toll-like receptor TLR2 (41), and recent findings suggest that Lrr domains are needed for this interaction (42). Thus, it may be that Lrr domains can serve as recognition motifs for other pattern recognition receptors as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they appear to be ideal ligands for a pattern recognition receptor. Interestingly, BspA interacts also with other pattern recognition receptors, such as the Toll-like receptor TLR2 (41), and recent findings suggest that Lrr domains are needed for this interaction (42). Thus, it may be that Lrr domains can serve as recognition motifs for other pattern recognition receptors as well.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 However, the importance of the TLR-mediated response during P gingivalismediated periodontal disease is unknown. Studies using Mycobacterium avium and Haemophilus influenzae support the proposition that bacterial infection leads to increased expression of TLRs 12,13 and that these TLRs play a role in further innate immune sensing during Crohn's disease and tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that these PRRs function as TLR-associated co-receptors that detect microbial pathogens or components thereof and present them to TLRs for activation of signaling pathways (19,21). In our efforts to determine the PRRs and the mechanisms involved in innate immune recognition of P. gingivalis fimbriae, we have found that CD14 directly binds fimbriae (22) and mediates their ability to stimulate TLR2-dependent TNF-␣ release (14,23). The ␤ 2 integrin CD11b/CD18 is also involved in P. gingivalis fimbriainduced cell activation (23), although it does not constitutively recognize this bacterial molecule (22).…”
mentioning
confidence: 99%
“…The multifunctional adhesive capacity of P. gingivalis fimbriae may result from versatile structural motifs, which in turn may offer pattern recognition substrate for the innate host defense. Indeed pattern recognition receptors (PRRs) 2 of the innate immune system can detect the presence of fimbriae and respond by inducing release of proinflammatory cytokines such as tumor necrosis factor-␣ (TNF-␣) (13)(14)(15).…”
mentioning
confidence: 99%